Base layer rapid repairing method for road collapse risk
Through the combination of gravel skeleton and special formula cement-based grouting materials, the problems of incomplete road collapse repair, long construction period and high cost in the existing technology are solved, and fast, efficient, economical and environmentally friendly road repair is achieved, and it is widely applicable. and excellent performance.
Patent Information
- Application Number
- CN202411440215.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing road collapse repair methods have problems such as incomplete repair, long construction period, high construction costs and great impact on the environment. It is difficult to quickly, economically and environmentally friendly to solve the needs of road repairs in varying degrees of collapse and various climatic conditions.
The combination method of gravel skeleton and special formula cement-based grouting material is used to form a high-performance composite repair structure by constructing gravel skeleton, formulating and injecting cement-based grouting material, performing curing and surface treatment.
It realizes rapid, economical and environmentally friendly road restoration, improves the strength, durability and deformation resistance of the repaired structure, reduces construction costs, is suitable for different degrees of collapse and various climatic conditions, and the repaired structure has excellent interface stickiness Junction performance and self-healing capability.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rapid road repair methods, and in particular to a rapid base repair method for road collapse risks. Background Art
[0002] In recent years, with the rapid development of infrastructure construction and the acceleration of urbanization in my country, road collapse has become an increasingly serious problem. This not only affects traffic safety, but also brings great challenges to urban management. Traditional methods for repairing road collapse mainly include grouting reinforcement, cement concrete slab reinforcement and overhaul and reconstruction. However, these methods have some defects that are difficult to overcome in practical applications.
[0003] Although the grouting reinforcement method is easy to operate, its repair effect is often unsatisfactory. This method is mainly suitable for repairing minor base voids. For serious structural damage, its repair effect is often not ideal. In addition, the bonding strength between the grouting material and the original pavement material is limited, and secondary damage is prone to occur, resulting in a short-lasting repair effect.
[0004] The cement concrete slab reinforcement method can restore the road surface function in a short period of time, but there are also many problems. First, the combination between the new and old materials is often not tight enough, which is prone to misalignment and overall detachment. Secondly, this method is often too costly for sections with less damage to the base layer and does not conform to the principle of economic efficiency. Finally, the shrinkage cracking of concrete is difficult to avoid, especially when repairing a large area.
[0005] Although the overhaul and reconstruction method can completely repair the base, its disadvantages are also very obvious. First, the construction period is long, which seriously affects the normal traffic order. Secondly, the project cost is high, which puts huge pressure on local finances. Moreover, large-scale excavation and reconstruction work will have a great impact on the surrounding environment, which is not in line with the current concept of green construction.
[0006] In the face of these problems, a road collapse repair method that is fast, efficient, economical and environmentally friendly is urgently needed. The present invention proposes an innovative solution to the problems of incomplete repair, long construction period and high construction cost in the prior art. Summary of the invention
[0007] The technical problems to be solved by the present invention mainly include: how to shorten the construction period while ensuring the quality of repair; how to improve the overall performance of the repair structure, including strength, durability and deformation resistance; how to reduce the cost of repair and reduce the impact on the environment; and how to make the repair method widely applicable and able to cope with different degrees of collapse and various climatic conditions.
[0008] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a method for rapid repair of a base layer for the risk of road collapse, comprising the following steps: first, constructing a crushed stone skeleton; second, preparing a cement-based grouting material; then, injecting the cement-based grouting material into the crushed stone skeleton; then, maintaining the grouting structure; and finally, performing surface treatment.
[0009] Preferably, the construction of the crushed stone skeleton comprises using crushed stones with a particle size of 20-40 mm, which are laid in grades according to the following weight ratios:
[0010] Crushed stone with a particle size of 20-25 mm: 30-40 parts by weight;
[0011] Crushed stone with a particle size of 25-30 mm: 30-40 parts by weight;
[0012] Crushed stone with a particle size of 30-40 mm: 20-40 parts by weight.
[0013] Preferably, the cement-based grouting material is composed of the following components, wherein the weight parts of each component are based on 100 weight parts of the total weight of the grouting material:
[0014] Ordinary Portland cement, with the designation PO 42.5, 60-70 parts by weight;
[0015] Class F fly ash, with a fineness of no more than 45 μm, 10-20 parts by weight;
[0016] Silica fume, with SiO2 content not less than 85% and specific surface area not less than 15000m 2 / kg, 5-10 parts by weight;
[0017] Polycarboxylic acid-based high-performance water reducer, 0.5-1.5 parts by weight;
[0018] Polyether defoamer, 0.1-0.3 parts by weight;
[0019] Polypropylene fibers, 6-12 mm in length and 15-30 μm in diameter, 0.1-0.3 parts by weight;
[0020] Water, 25-30 parts by weight.
[0021] Preferably, the preparation method of the cement-based grouting material comprises the following steps:
[0022] First, ordinary Portland cement, fly ash and silica fume are dry mixed for 2-3 minutes at a speed of 60-80 rpm;
[0023] Secondly, mix the polycarboxylic acid high performance water reducing agent with water and stir evenly;
[0024] Then, slowly add the above liquid to the dry mixed material, continue stirring for 5-7 minutes, and increase the speed to 100-120rpm;
[0025] Next, add the polyether defoamer and stir for 1-2 minutes;
[0026] Finally, add the polypropylene fibers and stir for 2-3 minutes to ensure that the fibers are evenly dispersed.
[0027] Preferably, the specific steps of the grouting construction include:
[0028] Use a high-pressure pump to inject the prepared grouting material into the crushed stone skeleton, where the grouting pressure is controlled at 0.2-0.5MPa;
[0029] Control the grouting speed at 10-15L / min;
[0030] An observation hole is set every 30-50cm to monitor the grouting effect.
[0031] Preferably, the specific steps of the maintenance include: covering the repair area with a plastic film; performing maintenance for 48-72 hours, during which the ambient temperature is maintained at 15-30°C and the relative humidity is not less than 90%; and watering the repair area once every 12 hours.
[0032] Preferably, the specific steps of the surface treatment include: laying a 4-6 cm thick modified asphalt concrete surface layer; wherein the modified asphalt concrete surface layer has the following composition, and the weight parts of each component are based on 100 weight parts of the total asphalt mixture:
[0033] SBS modified asphalt, with a penetration of 60-80 and a softening point of not less than 75°C, 4.5-5.5 parts by weight;
[0034] Coarse aggregate, made of basalt with a particle size of 9.5-19 mm, 50-60 parts by weight;
[0035] Fine aggregate, made of basalt with a particle size of 0-9.5 mm, 35-45 parts by weight;
[0036] Mineral powder, made of limestone with a particle size less than 0.075 mm, 3-5 parts by weight.
[0037] Preferably, the step of paving the modified asphalt concrete surface layer comprises:
[0038] Control the asphalt mixture paving temperature at 160-170℃;
[0039] Ensure that the rolling temperature is not lower than 140℃;
[0040] Use a 12-ton double steel wheel roller for rolling, with no less than 6 passes.
[0041] Preferably, the preparation method of the polycarboxylic acid-based high-performance water reducer comprises:
[0042] First, add 100 parts by weight of acrylic acid, 50-70 parts by weight of methallyl polyglycol ether and 200-300 parts by weight of deionized water into a four-necked flask;
[0043] Secondly, under nitrogen protection, the temperature was raised to 65-75°C, and the stirring speed was controlled at 300-400 rpm;
[0044] Then, 10-15 parts by weight of a 20 wt% ammonium persulfate initiator solution is slowly added dropwise;
[0045] Next, react for 4-6 hours and then cool to room temperature;
[0046] Finally, the pH was adjusted to 6-7 with sodium hydroxide solution.
[0047] Preferably, the preparation method of the polyether defoamer comprises:
[0048] First, add 100 parts by weight of ethylene oxide and 50-70 parts by weight of n-butanol into a reaction kettle;
[0049] Secondly, adding 0.5-1.0 parts by weight of potassium hydroxide as a catalyst;
[0050] Then, a ring-opening polymerization reaction is carried out at a temperature of 80-90° C. and a pressure of 0.3-0.5 MPa;
[0051] Next, after reacting for 6-8 hours, the mixture is cooled to room temperature and unreacted ethylene oxide is removed by decompression;
[0052] Finally, the beneficial effects of the present invention are:
[0053] The present invention innovatively combines the crushed stone skeleton with a specially formulated grouting material to form a high-performance composite repair structure, which not only solves various problems in traditional methods but also brings many unexpected technical effects.
[0054] First, the present invention achieves a perfect balance between repair quality and construction efficiency. The rapid construction of the crushed stone skeleton and the rapid solidification of the high-performance grouting material enable the entire repair process to be completed in a very short time, greatly reducing the impact on traffic. At the same time, the high strength characteristics of the composite structure ensure that the repair quality will not be affected by the rapid construction.
[0055] Secondly, the present invention significantly improves the overall performance of the repair structure. The crushed stone skeleton provides a stable load-bearing framework, while the specially formulated grouting material fills the skeleton gaps. The two work together to form a composite structure with strong integrity and uniform stress distribution. This not only improves the strength and deformation resistance of the repair structure, but also greatly enhances its durability.
[0056] Furthermore, the present invention is also excellent in terms of economy and environmental protection. Compared with major repair and reconstruction, this method greatly reduces the amount of materials used and construction costs. At the same time, since there is no need for large-scale excavation, the impact on the environment is greatly reduced, which is in line with the concept of green construction.
[0057] Finally, the method of the present invention has wide applicability. By adjusting the crushed stone grading and grouting material formula, it can adapt to different degrees of collapse. Moreover, the experimental results show that the method can maintain excellent performance under various climatic conditions, which makes it possible to promote and apply it nationwide.
[0058] In addition, the present invention also exhibits some unexpected technical effects. For example, the repair structure exhibits excellent interfacial bonding performance, which is due to the synergistic effect of the various components in the special formula grouting material. In addition, long-term observations have found that the repair structure also has a certain self-repairing ability, which is of great significance for extending the durability of the repair effect.
[0059] In summary, the present invention not only solves the problems existing in the prior art, but also achieves breakthroughs in performance in many aspects. It provides an innovative solution for the rapid, efficient and economical repair of road collapse, and has important practical application value and broad market prospects. DETAILED DESCRIPTION
[0060] Example 1
[0061] This embodiment provides a method for quickly repairing the base layer in response to the risk of road collapse. The method achieves quick repair of the road base layer by constructing a crushed stone skeleton and injecting cement-based grouting material with a specific ratio.
[0062] First, build a gravel skeleton. Select granite gravel with a particle size of 20-40mm and lay it in grades according to the following weight ratio: 30 parts by weight of 20-25mm gravel, 30 parts by weight of 25-30mm gravel, and 40 parts by weight of 30-40mm gravel. This graded laying method can optimize the porosity of the skeleton and create good conditions for subsequent grouting.
[0063] Secondly, a cement-based grouting material is prepared. The grouting material is composed of the following components (based on 100 parts by weight of the total amount of the grouting material): 70 parts by weight of ordinary Portland cement (PO 42.5), 10 parts by weight of Class F fly ash (fineness 45 μm), 10 parts by weight of silica fume (SiO2 content 85%, specific surface area 15000 m 2 / kg), 5 parts by weight, 0.5 parts by weight of polycarboxylic acid-based high-performance water reducing agent, 0.1 parts by weight of polyether defoaming agent, 0.1 parts by weight of polypropylene fiber (length 6 mm, diameter 15 μm), and 25 parts by weight of water.
[0064] The preparation method of cement-based grouting material comprises the following steps:
[0065] (1) First, ordinary Portland cement, fly ash and silica fume were dry mixed for 2 minutes at a speed of 60 rpm;
[0066] (2) Secondly, the polycarboxylic acid-based high-performance water reducer is mixed with water and stirred evenly;
[0067] (3) Then, the liquid in step (2) was slowly added to the dry mixed material in step (1), and stirring was continued for 5 minutes, and the rotation speed was increased to 100 rpm;
[0068] (4) Then, add a polyether defoamer and stir for 1 minute;
[0069] (5) Finally, add polypropylene fibers and stir for 2 minutes to ensure that the fibers are evenly dispersed.
[0070] Preferably, in an embodiment of the present invention, the preparation method of the polycarboxylic acid-based high-performance water reducer comprises the following steps:
[0071] (a) adding 100 parts by weight of acrylic acid, 50 parts by weight of methallyl polyglycol ether and 200 parts by weight of deionized water into a four-necked flask;
[0072] (b) Under nitrogen protection, the temperature was raised to 65°C and the stirring speed was 300 rpm;
[0073] (c) slowly adding dropwise 10 parts by weight of a 20 wt % ammonium persulfate initiator solution;
[0074] (d) react for 4 hours and cool to room temperature;
[0075] (e) Adjust the pH to 6 with sodium hydroxide solution.
[0076] The preparation method of the polyether defoamer comprises the following steps:
[0077] (a) adding 100 parts by weight of ethylene oxide and 50 parts by weight of n-butanol into a reaction kettle;
[0078] (b) adding 0.5 parts by weight of potassium hydroxide as a catalyst;
[0079] (c) performing a ring-opening polymerization reaction at a temperature of 80° C. and a pressure of 0.3 MPa;
[0080] (d) After reacting for 6 hours, the mixture was cooled to room temperature and unreacted ethylene oxide was removed by decompression;
[0081] (e) Neutralizing the catalyst with phosphoric acid.
[0082] Then, grouting construction is carried out. Use a high-pressure pump to inject the prepared grouting material into the gravel skeleton, the grouting pressure is controlled at 0.2MPa, and the grouting speed is controlled at 10L / min. An observation hole is set every 30cm to monitor the grouting effect. This grouting method can ensure that the grouting material fully fills the gaps between the gravel and forms an overall stable composite structure.
[0083] Next, the grouting structure is cured. Cover the repair area with plastic film and maintain the curing time for 48 hours, during which the ambient temperature is maintained at 15°C and the relative humidity is 90%. Sprinkle water on the repair area every 12 hours. This curing method can ensure that the cement-based grouting material is fully hydrated and reaches the expected strength.
[0084] Finally, the surface treatment is carried out. A 4cm thick modified asphalt concrete surface layer is laid, and the proportion is as follows (based on 100 parts by weight of asphalt mixture): 4.5 parts by weight of SBS modified asphalt (penetration 60, softening point 75°C), 60 parts by weight of coarse aggregate (basalt, particle size 9.5-19mm), 35 parts by weight of fine aggregate (basalt, particle size 0-9.5mm), and 3 parts by weight of mineral powder (limestone, particle size <0.075mm). The paving temperature of the asphalt mixture is controlled at 160°C, the rolling temperature is 140°C, and a 12-ton double steel wheel roller is used for rolling 6 times. This surface treatment method can ensure the flatness and durability of the road surface.
[0085] Example 2
[0086] This embodiment provides another method for rapid repair of base layer for road collapse risk. Based on the first embodiment, this method adjusts some parameters to adapt to different construction conditions.
[0087] First, build a gravel skeleton. Select limestone gravel with a particle size of 20-40mm and lay it in grade according to the following weight ratio: 35 parts by weight of 20-25mm gravel, 35 parts by weight of 25-30mm gravel, and 30 parts by weight of 30-40mm gravel. This grading method can further optimize the skeleton structure and improve overall stability.
[0088] Secondly, a cement-based grouting material is prepared. The grouting material is composed of the following components (based on 100 parts by weight of the total amount of the grouting material): 65 parts by weight of ordinary Portland cement (PO 42.5), 15 parts by weight of Class F fly ash (fineness 40 μm), silica fume (SiO2 content 90%, specific surface area 17000 m 2 / kg), 7 parts by weight, 1 part by weight of polycarboxylic acid-based high-performance water reducer, 0.2 parts by weight of polyether defoamer, 0.2 parts by weight of polypropylene fiber (length 9 mm, diameter 20 μm), and 27 parts by weight of water.
[0089] The preparation method of cement-based grouting material comprises the following steps:
[0090] (1) First, ordinary Portland cement, fly ash and silica fume were dry mixed for 2.5 minutes at a speed of 70 rpm;
[0091] (2) Secondly, the polycarboxylic acid-based high-performance water reducer is mixed with water and stirred evenly;
[0092] (3) Then, the liquid in step (2) was slowly added to the dry mixed material in step (1), and stirring was continued for 6 minutes, with the rotation speed increased to 110 rpm;
[0093] (4) Then, add a polyether defoamer and stir for 1.5 minutes;
[0094] (5) Finally, add polypropylene fibers and stir for 2.5 minutes to ensure that the fibers are evenly dispersed.
[0095] In this embodiment, the preparation method of the polycarboxylic acid-based high-performance water reducer comprises the following steps:
[0096] (a) adding 100 parts by weight of acrylic acid, 60 parts by weight of methallyl polyglycol ether and 250 parts by weight of deionized water into a four-necked flask;
[0097] (b) Under nitrogen protection, the temperature was raised to 70°C and the stirring speed was 350 rpm;
[0098] (c) slowly adding dropwise 12.5 parts by weight of a 20 wt % ammonium persulfate initiator solution;
[0099] (d) react for 5 hours and cool to room temperature;
[0100] (e) Adjust the pH to 6.5 with sodium hydroxide solution.
[0101] The preparation method of the polyether defoamer comprises the following steps:
[0102] (a) adding 100 parts by weight of ethylene oxide and 60 parts by weight of n-butanol into a reaction kettle;
[0103] (b) adding 0.75 parts by weight of potassium hydroxide as a catalyst;
[0104] (c) performing a ring-opening polymerization reaction at a temperature of 85° C. and a pressure of 0.4 MPa;
[0105] (d) After reacting for 7 hours, the mixture was cooled to room temperature and unreacted ethylene oxide was removed by decompression;
[0106] (e) Neutralizing the catalyst with phosphoric acid.
[0107] Then, grouting construction is carried out. Use a high-pressure pump to inject the prepared grouting material into the crushed stone skeleton, the grouting pressure is controlled at 0.35MPa, and the grouting speed is controlled at 12.5L / min. An observation hole is set every 40cm to monitor the grouting effect. This adjustment of grouting parameters can improve grouting efficiency and ensure grouting quality.
[0108] Next, the grouting structure is cured. Cover the repair area with plastic film and maintain the curing time for 60 hours, during which the ambient temperature is maintained at 22°C and the relative humidity is 95%. Sprinkle water on the repair area every 12 hours. Extending the curing time and increasing the humidity can further improve the strength of the repair.
[0109] Finally, the surface treatment is carried out. A 5cm thick modified asphalt concrete surface layer is laid, and the proportion is as follows (based on 100 parts by weight of asphalt mixture): 5 parts by weight of SBS modified asphalt (needle penetration 70, softening point 78°C), 55 parts by weight of coarse aggregate (basalt, particle size 9.5-19mm), 40 parts by weight of fine aggregate (basalt, particle size 0-9.5mm), and 4 parts by weight of mineral powder (limestone, particle size <0.075mm). The paving temperature of the asphalt mixture is controlled at 165°C, the rolling temperature is 145°C, and a 12-ton double steel wheel roller is used for rolling 8 times. This adjustment can improve the road surface's deformation resistance and durability.
[0110] Example 3
[0111] This embodiment provides a third method for rapid repair of the base layer for road collapse risk. This method further optimizes the material ratio and construction parameters for more serious collapse situations.
[0112] First, build a gravel skeleton. Select granite gravel with a particle size of 20-40mm and lay it in grade according to the following weight ratio: 40 parts by weight of 20-25mm gravel, 40 parts by weight of 25-30mm gravel, and 20 parts by weight of 30-40mm gravel. This grading method increases the proportion of small-size gravel and improves the density of the skeleton.
[0113] Secondly, a cement-based grouting material is prepared. The grouting material is composed of the following components (based on 100 parts by weight of the total amount of the grouting material): 67 parts by weight of ordinary Portland cement (PO 42.5), 18 parts by weight of Class F fly ash (fineness 42 μm), 18 parts by weight of silica fume (SiO2 content 88%, specific surface area 16000 m 2 / kg), 8 parts by weight, 1.2 parts by weight of polycarboxylic acid-based high-performance water reducer, 0.25 parts by weight of polyether defoamer, 0.25 parts by weight of polypropylene fiber (length 10 mm, diameter 25 μm), and 28 parts by weight of water.
[0114] The preparation method of cement-based grouting material comprises the following steps:
[0115] (1) First, ordinary Portland cement, fly ash and silica fume were dry mixed for 3 minutes at a speed of 75 rpm;
[0116] (2) Secondly, the polycarboxylic acid-based high-performance water reducer is mixed with water and stirred evenly;
[0117] (3) Then, the liquid in step (2) was slowly added to the dry mixed material in step (1), and stirring was continued for 6.5 minutes, and the rotation speed was increased to 115 rpm;
[0118] (4) Then, add a polyether defoamer and stir for 1.8 minutes;
[0119] (5) Finally, add polypropylene fibers and stir for 2.8 minutes to ensure that the fibers are evenly dispersed.
[0120] In this embodiment, the preparation method of the polycarboxylic acid-based high-performance water reducer comprises the following steps:
[0121] (a) adding 100 parts by weight of acrylic acid, 65 parts by weight of methallyl polyglycol ether and 275 parts by weight of deionized water into a four-necked flask;
[0122] (b) Under nitrogen protection, the temperature was raised to 72°C and the stirring speed was 375 rpm;
[0123] (c) slowly adding dropwise 13.5 parts by weight of a 20 wt % ammonium persulfate initiator solution;
[0124] (d) reacting for 5.5 hours and cooling to room temperature;
[0125] (e) Adjust the pH to 6.8 with sodium hydroxide solution.
[0126] The preparation method of the polyether defoamer comprises the following steps:
[0127] (a) adding 100 parts by weight of ethylene oxide and 65 parts by weight of n-butanol into a reaction kettle;
[0128] (b) adding 0.85 parts by weight of potassium hydroxide as a catalyst;
[0129] (c) performing a ring-opening polymerization reaction at a temperature of 87° C. and a pressure of 0.45 MPa;
[0130] (d) After reacting for 7.5 hours, the mixture was cooled to room temperature and unreacted ethylene oxide was removed by decompression;
[0131] (e) Neutralizing the catalyst with phosphoric acid.
[0132] Then, grouting construction is carried out. Use a high-pressure pump to inject the prepared grouting material into the crushed stone skeleton, and the grouting pressure is controlled at 0.4MPa and the grouting speed is controlled at 13.5L / min. An observation hole is set every 35cm to monitor the grouting effect. This adjustment of grouting parameters can further improve the grouting efficiency and filling degree, and is suitable for more serious collapse situations.
[0133] Next, the grouting structure is cured. The repair area is covered with plastic film and the curing time is 66 hours. During this period, the ambient temperature is maintained at 25°C and the relative humidity is 98%. The repair area is watered every 12 hours. This optimization of curing conditions can promote cement hydration reaction and improve the strength and durability of the repair.
[0134] Finally, the surface treatment is carried out. A 5.5 cm thick modified asphalt concrete surface layer is laid, and the proportion is as follows (based on 100 parts by weight of asphalt mixture): 5.2 parts by weight of SBS modified asphalt (penetration 75, softening point 80°C), 52 parts by weight of coarse aggregate (basalt, particle size 9.5-19mm), 42 parts by weight of fine aggregate (basalt, particle size 0-9.5mm), and 4.5 parts by weight of mineral powder (limestone, particle size <0.075mm). The paving temperature of the asphalt mixture is controlled at 168°C, the rolling temperature is 148°C, and a 12-ton double steel wheel roller is used for rolling, and rolling is performed 9 times. This adjustment can further improve the road surface's anti-deformation ability, durability and anti-rutting performance.
[0135] Example 4
[0136] This embodiment provides a fourth method for rapid repair of the base layer for road collapse risk. This method is suitable for road repair under special climatic conditions, such as cold areas or hot and rainy areas.
[0137] First, build a gravel skeleton. Select basalt gravel with a particle size of 20-40mm and lay it in grade according to the following weight ratio: 38 parts by weight of 20-25mm gravel, 38 parts by weight of 25-30mm gravel, and 24 parts by weight of 30-40mm gravel. This grading method and material selection can improve the freeze-thaw resistance and overall stability of the skeleton.
[0138] Secondly, a cement-based grouting material is prepared. The grouting material is composed of the following components (based on 100 parts by weight of the total amount of the grouting material): 62 parts by weight of ordinary Portland cement (PO 42.5), 20 parts by weight of Class F fly ash (fineness 38 μm), silica fume (SiO2 content 92%, specific surface area 18000 m 2 / kg), 10 parts by weight of polycarboxylic acid high-performance water reducing agent, 1.5 parts by weight of polyether defoaming agent, 0.3 parts by weight of polypropylene fiber (length 12 mm, diameter 30 μm), 0.3 parts by weight of water.
[0139] The preparation method of cement-based grouting material comprises the following steps:
[0140] (1) First, ordinary Portland cement, fly ash and silica fume were dry mixed for 3 minutes at a speed of 80 rpm;
[0141] (2) Secondly, the polycarboxylic acid-based high-performance water reducer is mixed with water and stirred evenly;
[0142] (3) Then, the liquid in step (2) was slowly added to the dry mixed material in step (1), and stirring was continued for 7 minutes, and the rotation speed was increased to 120 rpm;
[0143] (4) Then, add a polyether defoamer and stir for 2 minutes;
[0144] (5) Finally, add polypropylene fibers and stir for 3 minutes to ensure that the fibers are evenly dispersed.
[0145] In this embodiment, the preparation method of the polycarboxylic acid-based high-performance water reducer comprises the following steps:
[0146] (a) adding 100 parts by weight of acrylic acid, 70 parts by weight of methallyl polyglycol ether and 300 parts by weight of deionized water into a four-necked flask;
[0147] (b) Under nitrogen protection, the temperature was raised to 75°C and the stirring speed was 400 rpm;
[0148] (c) slowly adding dropwise 15 parts by weight of a 20 wt % ammonium persulfate initiator solution;
[0149] (d) react for 6 hours and cool to room temperature;
[0150] (e) Adjust the pH to 7 with sodium hydroxide solution.
[0151] The preparation method of the polyether defoamer comprises the following steps:
[0152] (a) adding 100 parts by weight of ethylene oxide and 70 parts by weight of n-butanol into a reaction kettle;
[0153] (b) adding 1.0 parts by weight of potassium hydroxide as a catalyst;
[0154] (c) performing a ring-opening polymerization reaction at a temperature of 90° C. and a pressure of 0.5 MPa;
[0155] (d) After reacting for 8 hours, the mixture was cooled to room temperature and unreacted ethylene oxide was removed by decompression;
[0156] (e) Neutralizing the catalyst with phosphoric acid.
[0157] Then, grouting construction is carried out. Use a high-pressure pump to inject the prepared grouting material into the crushed stone skeleton, the grouting pressure is controlled at 0.5MPa, and the grouting speed is controlled at 15L / min. An observation hole is set every 50cm to monitor the grouting effect. This adjustment of grouting parameters can ensure the full penetration and filling of the grouting material under special climatic conditions.
[0158] Next, the grouting structure is cured. Cover the repair area with plastic film and maintain the curing time for 72 hours. During this period, the ambient temperature is maintained at 30°C (for high temperature areas) or 10°C (for cold areas) and the relative humidity is 100%. Sprinkle water on the repair area every 8 hours. This adjustment of curing conditions can adapt to different climatic conditions and ensure that the cement is fully hydrated and reaches the expected strength.
[0159] Finally, the surface treatment is carried out. A 6cm thick modified asphalt concrete surface layer is laid, and the proportion is as follows (based on 100 parts by weight of asphalt mixture): 5.5 parts by weight of SBS modified asphalt (penetration 80, softening point 82°C), 50 parts by weight of coarse aggregate (basalt, particle size 9.5-19mm), 45 parts by weight of fine aggregate (basalt, particle size 0-9.5mm), and 5 parts by weight of mineral powder (limestone, particle size <0.075mm). The paving temperature of the asphalt mixture is controlled at 170°C, the rolling temperature is 150°C, and a 12-ton double steel wheel roller is used for rolling 10 times. This adjustment can improve the adaptability and durability of the road surface under extreme climatic conditions.
[0160] It is worth noting that each component plays an important role in the entire repair process. For example, polycarboxylic acid-based high-performance water reducers disperse cement particles through electrostatic repulsion and steric hindrance, improve the fluidity of the grouting material, and ensure that the grouting material can fully penetrate into the pores of the gravel skeleton. Polyether defoamers eliminate bubbles by reducing surface tension, increase the density of the grouting material, and thus enhance the overall strength of the repaired structure. The addition of polypropylene fibers significantly improves the crack resistance and toughness of the repaired structure, helping to prevent cracking and damage to the repaired road surface.
[0161] This multi-component synergistic repair method can not only quickly restore the road's bearing capacity, but also provide excellent durability. By adjusting the proportions of each component and preparation parameters, the method of the present invention can flexibly respond to different types and degrees of road collapse, providing an efficient, economical and adaptable solution for road maintenance and repair.
[0162] Comparative Example 1
[0163] This comparative example provides a traditional road collapse repair method for comparison with Example 1. This method uses only ordinary cement slurry for grouting, without using crushed stone skeleton and composite grouting material.
[0164] First, prepare ordinary cement slurry. The slurry consists of the following components (based on 100 parts by weight of the total slurry): 70 parts by weight of ordinary Portland cement (PO 42.5) and 30 parts by weight of water.
[0165] The preparation method of cement slurry comprises the following steps:
[0166] (1) Add ordinary Portland cement into a mixer;
[0167] (2) Slowly add water while stirring;
[0168] (3) Stir for 5 minutes at 60 rpm.
[0169] Then, grouting construction is carried out. A conventional grouting pump is used to inject the prepared cement slurry into the collapsed area, and the grouting pressure is controlled at 0.2MPa and the grouting speed is controlled at 10L / min.
[0170] Next, the grouting structure is cured. The repair area is covered with plastic film and the curing time is 48 hours, during which the ambient temperature is maintained at 20°C and the relative humidity is 85%.
[0171] Finally, the surface treatment was carried out. A 4 cm thick ordinary asphalt concrete surface layer was laid, with the following proportions (based on 100 parts by weight of asphalt mixture): 5 parts by weight of ordinary road petroleum asphalt (penetration 60, softening point 48°C), 55 parts by weight of coarse aggregate, and 40 parts by weight of fine aggregate. The asphalt mixture paving temperature was controlled at 150°C, the rolling temperature was 130°C, and an 8-ton double steel wheel roller was used for rolling 6 times.
[0172] Compared with Example 1, this comparative example lacks the synergistic effect of the crushed stone skeleton and the composite grouting material. This results in lower overall strength and stability of the repaired structure and poor crack resistance. At the same time, due to the lack of high-performance water reducer and defoamer, the fluidity and density of the slurry are poor, and the gaps in the collapsed area cannot be fully filled. In addition, the deformation resistance and durability of the ordinary asphalt surface layer are not as good as those of the modified asphalt surface layer.
[0173] Comparative Example 2
[0174] This comparative example provides a road collapse repair method using only crushed stone filling for comparison with Example 2. This method does not use grouting material, but relies entirely on crushed stone filling to restore the roadbed strength.
[0175] First, limestone crushed stones with a particle size of 20-40 mm are selected and graded and filled according to the following weight ratio: 35 parts by weight of crushed stones with a particle size of 20-25 mm, 35 parts by weight of crushed stones with a particle size of 25-30 mm, and 30 parts by weight of crushed stones with a particle size of 30-40 mm.
[0176] The filling method includes the following steps:
[0177] (1) Pour the crushed stone into the collapsed area in layers;
[0178] (2) Each layer is about 20 cm thick and is compacted using a vibratory roller;
[0179] (3) Repeat steps (1) and (2) until the collapsed area is filled.
[0180] Then, the filled structure is cured for 24 hours, during which the ambient temperature is maintained at 22°C and the relative humidity is 70%.
[0181] Finally, the surface was treated by laying a 5 cm thick common asphalt concrete surface layer, with the same proportion as in comparative example 1. The asphalt mixture paving temperature was controlled at 155°C, the rolling temperature was 135°C, and a 10-ton double steel wheel roller was used for rolling 7 times.
[0182] Compared with Example 2, although graded crushed stones are used in this comparative example, the bonding strength between the crushed stones is low due to the lack of bonding effect of the grouting material. This leads to uneven settlement or loosening of the filling structure under long-term load. At the same time, since no cement-based grouting material is used, the overall strength and deformation resistance of the repaired structure are poor. In addition, the performance of the ordinary asphalt surface layer is not as good as the modified asphalt surface layer in Example 2.
[0183] Comparative Example 3
[0184] This comparative example provides a road collapse repair method using ordinary concrete pouring, which is used for comparison with Example 3. This method does not use a crushed stone skeleton and grouting material, but directly fills the collapsed area with concrete.
[0185] First, prepare ordinary concrete. The concrete mix is as follows (based on 1m 3 Concrete meter):
[0186] Ordinary Portland cement (PO 42.5) 350kg, coarse aggregate (5-20mm crushed stone) 1150kg, fine aggregate (river sand) 750kg, water 160kg.
[0187] The method for preparing concrete comprises the following steps:
[0188] (1) Add coarse aggregate and fine aggregate into a mixer and dry mix for 30 seconds;
[0189] (2) Add cement and continue dry mixing for 30 seconds;
[0190] (3) Add water and mix for 2 minutes.
[0191] Then, pour the concrete. Use a concrete pump to pump the prepared concrete to the collapsed area and pour it in layers, with each layer about 30cm thick. Use an inserted vibrator to vibrate and ensure that the concrete is fully compacted.
[0192] Next, the poured structure is cured for 7 days, during which the ambient temperature is kept at 25°C and the relative humidity is 90%. Water is sprinkled 3 times a day to keep the surface moist.
[0193] Finally, the surface was treated by laying a 5 cm thick common asphalt concrete surface layer, with the same proportion as in comparative example 1. The asphalt mixture paving temperature was controlled at 160°C, the rolling temperature was 140°C, and a 12-ton double steel wheel roller was used for rolling 8 times.
[0194] Compared with Example 3, although this comparative example can provide higher strength, it has the following problems: First, the risk of shrinkage cracking of concrete is higher, especially when repairing a large area. Second, the crack resistance and toughness of ordinary concrete are not as good as the composite structure in Example 3. Furthermore, the curing time of concrete is long, which seriously affects the normal use of the road. Finally, the bond between the concrete structure and the original roadbed is not tight enough, which easily causes stress concentration and leads to cracking at the edge of the repair area.
[0195] Comparative Example 4
[0196] This comparative example provides a road collapse repair method using modified asphalt mixture for direct filling, which is used for comparison with Example 4. This method does not use a crushed stone skeleton and grouting material, but directly fills the collapsed area with modified asphalt mixture.
[0197] First, prepare the modified asphalt mixture. The proportion is as follows (based on 100 parts by weight of asphalt mixture):
[0198] 5.5 parts by weight of SBS modified asphalt (penetration 70, softening point 76°C), 50 parts by weight of coarse aggregate (basalt, particle size 9.5-19 mm), 44 parts by weight of fine aggregate (basalt, particle size 0-9.5 mm), and 5 parts by weight of mineral powder (limestone, particle size <0.075 mm).
[0199] The preparation method of modified asphalt mixture comprises the following steps:
[0200] (1) heating the coarse aggregate and the fine aggregate to 170°C;
[0201] (2) heating the SBS modified asphalt to 160°C;
[0202] (3) Add the heated aggregate, modified asphalt and mineral powder into an asphalt mixer and mix for 3 minutes.
[0203] Then, fill construction is carried out. The hot asphalt mixture is transported to the construction site and directly spread on the collapsed area using a paver. It is spread in layers, with each layer being about 8cm thick.
[0204] Then, a 12-ton double-steel-wheel roller was used for rolling, with the rolling temperature controlled at 150°C and rolling for 9 times. The curing time is 24 hours, during which time vehicles are prohibited from passing.
[0205] Finally, a 4cm thick modified asphalt concrete surface layer is laid on the surface of the filling layer, with the same proportion as the filling layer. The paving temperature is controlled at 165℃, the rolling temperature is 145℃, and the rolling is carried out 8 times.
[0206] Compared with Example 4, although this comparative example uses a high-performance modified asphalt mixture, the following problems still exist: First, a single asphalt mixture structure is prone to permanent deformation when subjected to heavy traffic, resulting in rutting on the road surface. Second, asphalt materials are highly temperature sensitive, and their performance will drop significantly under extreme climatic conditions (such as high or low temperature environments). Furthermore, the bonding strength between the asphalt mixture and the underlying roadbed is weak, resulting in interlayer voids. Finally, this method is difficult to effectively fill deep collapses, especially when the collapse depth is large.
[0207] Through these four comparative examples, the superiority of the method of the present invention can be clearly seen. The present invention adopts a method of combining a crushed stone skeleton with a specially formulated grouting material, giving full play to the advantages of each component, and forming a composite repair structure with high strength, high stability and high durability. This structure can not only quickly restore the bearing capacity of the road, but also has excellent anti-deformation and anti-cracking properties. At the same time, the method of the present invention has a fast construction speed and a short maintenance time, which greatly reduces the impact on traffic. These advantages can be reflected under different climatic conditions and collapse degrees, reflecting the wide applicability and high efficiency of the method of the present invention.
[0208] In order to comprehensively evaluate the effectiveness and superiority of the present invention "a method for rapid repair of base course for road collapse risk", the present invention has designed a series of test experiments. These experiments are intended to verify the core innovation of the present invention, namely the performance of the composite repair structure combining the crushed stone skeleton with the specially formulated grouting material. The following is a detailed experimental design, method, results and analysis:
[0209] 1. Compressive strength test
[0210] Experimental method: According to GB / T 50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", a 100mm×100mm×100mm cubic specimen was made. The grouting material was injected into the pre-prepared gravel skeleton, and the compressive strength test was carried out after curing for 28 days.
[0211] Experimental steps:
[0212] First, place the specimen on a universal testing machine. Second, apply a load evenly at a loading rate of 0.5-0.8MPa / s. Then, record the maximum load at which the specimen fails. Finally, calculate the compressive strength.
[0213] 2. Flexural strength test
[0214] Experimental method: Referring to GB / T 50081-2019, a 100mm×100mm×400mm prism specimen was made. A three-point bending test was performed after curing for 28 days.
[0215] Experimental steps:
[0216] First, place the specimen on the flexural testing machine with a support distance of 300mm. Second, apply the load evenly at a loading rate of 0.05MPa / s. Then, record the maximum load when the specimen fails. Finally, calculate the flexural strength.
[0217] 3. Shrinkage test
[0218] Experimental method: Referring to GB / T 50082-2009 “Standard for test methods of long-term performance and durability of ordinary concrete”, a 100mm×100mm×515mm prism specimen was made, and probes were buried at both ends.
[0219] Experimental steps:
[0220] First, the initial length measurement is performed immediately after the specimen is demoulded. Secondly, the specimen is placed in a standard curing room (temperature 20±2℃, relative humidity 60±5%). Then, the length is measured at 1d, 3d, 7d, 14d, 28d, 56d, and 90d. Finally, the shrinkage rate at each age is calculated.
[0221] 4. Anti-seepage performance test
[0222] Experimental method: Referring to GB / T 50082-2009, a cylindrical specimen of Φ150mm×150mm was made. After curing for 28 days, the anti-seepage performance test was carried out.
[0223] Experimental steps:
[0224] First, install the specimen on the water-resistance meter. Then, pressurize it step by step at a rate of 0.1MPa / h, and maintain each pressure for 8 hours. Then, when the water pressure reaches 1.2MPa, maintain it for 72 hours. Finally, split the specimen and measure the water seepage depth.
[0225] 5. Freeze-thaw resistance test
[0226] Experimental method: According to GB / T 50082-2009, 100mm×100mm×400mm prism specimens were made. Freeze-thaw cycle test was carried out after 28 days of curing.
[0227] Experimental steps:
[0228] First, immerse the specimen in water for 24 hours. Second, perform freeze-thaw cycles (-18°C to 5°C, 4 hours per cycle). Then, measure the relative dynamic elastic modulus after every 25 cycles. Finally, perform 300 cycles or stop the test when the relative dynamic elastic modulus is less than 60%.
[0229] The test results are as follows:
[0230] Table 1: Compressive strength, flexural strength and 28-day shrinkage of each specimen
[0231] Test piece Compressive strength(MPa) Flexural strength(MPa) <![CDATA[28-day shrinkage rate (×10 -6 )]]> Example 1 45.6 5.8 386 Example 2 48.2 6.2 372 Example 3 52.7 6.7 358 Example 4 50.9 6.5 365 Comparative Example 1 32.1 4.1 528 Comparative Example 2 28.5 3.6 not applicable Comparative Example 3 40.3 5.2 462 Comparative Example 4 35.7 4.8 not applicable
[0232] Table 2: Anti-permeability and freeze-thaw resistance of each specimen
[0233] Test piece Impermeability grade Relative dynamic elastic modulus after 300 freeze-thaw cycles (%) Example 1 P10 92 Example 2 P10 94 Example 3 P12 96 Example 4 P12 95 Comparative Example 1 P6 78 Comparative Example 2 P4 65 Comparative Example 3 P8 86 Comparative Example 4 P6 72
[0234] The results are analyzed as follows:
[0235] 1. Mechanical properties: As can be seen from Table 1, Examples 1-4 of the present invention all exhibit excellent compressive strength and flexural strength. In particular, Example 3 has a compressive strength of 52.7 MPa and a flexural strength of 6.7 MPa, far exceeding all comparative examples. This proves that the composite structure combining the crushed stone skeleton and the specially formulated grouting material has significant mechanical property advantages.
[0236] 2. Shrinkage performance: The 28-day shrinkage of Examples 1-4 of the present invention is significantly lower than that of Comparative Examples 1 and 3. This shows that the method of the present invention can effectively control the shrinkage of the repaired structure and reduce the risk of cracking. It is worth noting that Comparative Examples 2 and 4 are not suitable for shrinkage test because they do not contain cement-based materials.
[0237] 3. Impermeability: Examples 1-4 all achieved an impermeability rating of P10 or higher, while the impermeability ratings of the comparative examples were generally lower. This indicates that the composite structure formed by the method of the present invention has excellent compactness and impermeability, which is beneficial to improving the durability of the repaired structure.
[0238] 4. Freeze-thaw resistance: After 300 freeze-thaw cycles, the relative dynamic elastic modulus of Examples 1-4 remained above 92%, much higher than that of the comparative example. This indicates that the repair structure formed by the method of the present invention has excellent freeze-thaw resistance and is suitable for road repair in severe cold regions.
[0239] Based on the above test results, Example 3 can be considered as the best example, which has the best performance in mechanical properties, shrinkage control, impermeability and freeze-thaw resistance.
[0240] The present invention has the following unexpected technical effects:
[0241] 1. Super high early strength: Although the test results show the strength at 28 days, it is found in actual application that the repair structure formed by the method of the present invention can reach a strength sufficient to withstand normal traffic loads within 3 days. This greatly shortens the maintenance time of road repair and reduces traffic interruption.
[0242] 2. Excellent interfacial bonding performance: During the test, it was found that the composite structure formed by the method of the present invention has extremely high bonding strength with the original roadbed material. This is due to the synergistic effect of the ultrafine silica fume and high-performance water reducing agent in the specially formulated grouting material, which improves the fluidity and bonding of the grouting material.
[0243] 3. Self-repairing ability: Long-term observations have shown that the repair structure formed by the method of the present invention has a certain self-repairing ability. This is because the cement particles that are not completely hydrated in the grouting material continue to hydrate when microcracks appear, thereby filling the cracks.
[0244] 4. Excellent anti-fatigue performance: Although fatigue performance tests were not included in this test, it was observed in actual application that the road section repaired by the method of the present invention had minimal deformation under long-term repeated loads. This is because the crushed stone skeleton provides a stable support structure, while the specially formulated grouting material fills the skeleton gaps, forming a composite structure with strong integrity and uniform stress distribution.
[0245] 5. Environmental adaptability: Test results show that the method of the present invention not only performs well at room temperature, but also maintains good performance in high and low temperature environments. This full temperature range adaptability allows the method of the present invention to be widely used in road repair in different climate regions.
[0246] In summary, the method of the present invention not only achieves rapid and high-strength road repair through the innovative combination of crushed stone skeleton and specially formulated grouting material, but also performs well in durability, environmental adaptability, etc. These excellent performances and unexpected technical effects make the method of the present invention have important application prospects in the field of road maintenance and repair.
[0247] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for rapid repair of base layer for road collapse risk, characterized in that: The following steps are involved: First, construct a rubble skeleton; Secondly, prepare cement-based grouting material; Then, the cement-based grouting material is injected into the crushed stone skeleton; then, the grouting structure is cured; and finally, surface treatment is performed.
2. The method according to claim 1, characterized in that The construction of the crushed stone skeleton includes using crushed stones with a particle size of 20-40 mm, which are graded and laid according to the following weight ratios: Crushed stone with a particle size of 20-25 mm: 30-40 parts by weight; Crushed stone with a particle size of 25-30 mm: 30-40 parts by weight; Crushed stone with a particle size of 30-40 mm: 20-40 parts by weight.
3. The method according to claim 1, characterized in that The cement-based grouting material is composed of the following components, wherein the weight parts of each component are based on 100 weight parts of the total weight of the grouting material: Ordinary Portland cement, with the designation PO 42.5, 60-70 parts by weight; Class F fly ash, with a fineness of no more than 45 μm, 10-20 parts by weight; Silica fume, with SiO2 content not less than 85% and specific surface area not less than 15000m 2 / kg, 5-10 parts by weight; Polycarboxylic acid-based high-performance water reducer, 0.5-1.5 parts by weight; Polyether defoamer, 0.1-0.3 parts by weight; Polypropylene fibers, 6-12 mm in length and 15-30 μm in diameter, 0.1-0.3 parts by weight; Water, 25-30 parts by weight.
4. The method according to claim 3, characterized in that The preparation method of the cement-based grouting material comprises the following steps: First, ordinary Portland cement, fly ash and silica fume are dry mixed for 2-3 minutes at a speed of 60-80 rpm; Secondly, mix the polycarboxylic acid high performance water reducing agent with water and stir evenly; Then, slowly add the above liquid to the dry mixed material, continue stirring for 5-7 minutes, and increase the speed to 100-120rpm; Next, add the polyether defoamer and stir for 1-2 minutes; Finally, add the polypropylene fibers and stir for 2-3 minutes to ensure that the fibers are evenly dispersed.
5. The method according to claim 1, characterized in that The specific steps of the grouting construction include: Use a high-pressure pump to inject the prepared grouting material into the crushed stone skeleton, where the grouting pressure is controlled at 0.2-0.5MPa; Control the grouting speed at 10-15L / min; An observation hole is set every 30-50cm to monitor the grouting effect.
6. The method according to claim 1, characterized in that The specific steps of the maintenance include: covering the repair area with a plastic film; performing maintenance for 48-72 hours, during which the ambient temperature is maintained at 15-30°C and the relative humidity is not less than 90%; and watering the repair area once every 12 hours.
7. The method according to claim 1, characterized in that The specific steps of the surface treatment include: laying a 4-6 cm thick modified asphalt concrete surface layer; wherein the modified asphalt concrete surface layer has the following proportions, with the weight parts of each component being based on 100 parts by weight of the total amount of the asphalt mixture: SBS modified asphalt, with a penetration of 60-80 and a softening point of not less than 75°C, 4.5-5.5 parts by weight; Coarse aggregate, made of basalt with a particle size of 9.5-19 mm, 50-60 parts by weight; Fine aggregate, made of basalt with a particle size of 0-9.5 mm, 35-45 parts by weight; Mineral powder, made of limestone with a particle size less than 0.075 mm, 3-5 parts by weight.
8. The method according to claim 7, characterized in that The paving steps of the modified asphalt concrete surface layer include: Control the asphalt mixture paving temperature at 160-170℃; Ensure that the rolling temperature is not lower than 140℃; Use a 12-ton double steel wheel roller for rolling, with no less than 6 passes.
9. The method according to claim 3, characterized in that: The preparation method of the polycarboxylic acid high performance water reducing agent comprises: First, add 100 parts by weight of acrylic acid, 50-70 parts by weight of methallyl polyglycol ether and 200-300 parts by weight of deionized water into a four-necked flask; Secondly, under nitrogen protection, the temperature was raised to 65-75°C, and the stirring speed was controlled at 300-400 rpm; Then, 10-15 parts by weight of a 20 wt% ammonium persulfate initiator solution is slowly added dropwise; Next, react for 4-6 hours and then cool to room temperature; Finally, the pH was adjusted to 6-7 with sodium hydroxide solution.
10. The method according to claim 3, characterized in that: The preparation method of the polyether defoamer comprises: First, add 100 parts by weight of ethylene oxide and 50-70 parts by weight of n-butanol into a reaction kettle; Secondly, adding 0.5-1.0 parts by weight of potassium hydroxide as a catalyst; Then, a ring-opening polymerization reaction is carried out at a temperature of 80-90° C. and a pressure of 0.3-0.5 MPa; Next, after reacting for 6-8 hours, the mixture is cooled to room temperature and unreacted ethylene oxide is removed by decompression; Finally, the catalyst is neutralized with phosphoric acid.
Citation Information
Patent Citations
Modified water reducing agent with high slump loss resistance, and preparation method thereof
CN112125560A
UHPC (Ultra High Performance Concrete) board prepared from construction waste and preparation method of UHPC board
CN115611576A
Rapid maintenance method for local damage of base layer based on gravel grouting material
CN116927030A
High pulverization resistant backfill grout and backfill grout material thereof
JP2019011233A
Fiber composite pouring flexible waterproof pavement for bridges and tunnels and construction method
WO2022126573A1